2003
DOI: 10.1080/14660820310012745
|View full text |Cite
|
Sign up to set email alerts
|

Reduced p75NTRexpression delays disease onset only in female mice of a transgenic model of familial amyotrophic lateral sclerosis

Abstract: hSOD1 (G93A) transgenic mice develop pathological changes similar to those in patients with familial amyotrophic lateral sclerosis (FALS). In particular, the progressive degeneration of motoneurons is charactered in this mouse model. One feature of stressed motoneurons in ALS and the hSOD1 mice is the induction of the p75 neurotrophin receptor, which is thought, under certain circumstances, to be a death-signaling molecule. We have studied disease progression of hSOD1 (G93A) mice in the absence of the p75NTR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…A critical role of p75 NTR , a member of the TNF superfamily, in mediating neuronal death has been documented in models of neurodegenerative diseases, including diabetes [47][48][49]. In agreement, our results showed that diabetes stimulates p38MAPK phosphorylation and cleaved PARP in vivo, and that high glucose stimulates p75 NTR and NTR using siRNA blocked these effects in NG and HG media (n=3).…”
Section: Discussionsupporting
confidence: 80%
“…A critical role of p75 NTR , a member of the TNF superfamily, in mediating neuronal death has been documented in models of neurodegenerative diseases, including diabetes [47][48][49]. In agreement, our results showed that diabetes stimulates p38MAPK phosphorylation and cleaved PARP in vivo, and that high glucose stimulates p75 NTR and NTR using siRNA blocked these effects in NG and HG media (n=3).…”
Section: Discussionsupporting
confidence: 80%
“…However, crossing the SOD1 G93A mice with p75 − / − mice provided only partial protection in females [79]. These results are complicated by the multifaceted role of the receptor in other cells that could affect motor neuron viability (e.g.…”
Section: Retrograde Degenerative Signalingmentioning
confidence: 79%
“…Reductions in p75NTR expression and subsequent caspase activation in spinal cord were consistent with increased neuronal survival in antisense nucleic acid-treated mice, indicating that p75NTR might be a promising target for antisense nucleic acid treatment. Reduced p75NTR expression also delayed disease onset in a transgenic hSOD1 (G93A) mouse model of ALS, and increased motoneuronal survival correlated with less astrocytic activation in spinal cord [84]. In addition, a complete deletion of p75NTR resulted in long-lasting increases in the number of basal forebrain cholinergic neurons in p75NTR gene knockout mice [21].…”
Section: Prospect On the Prongf-p75ntr-sortilin Signalling Complex Asmentioning
confidence: 97%